Ferromagnetic Materials: Gigantic Current Control of Coercive Field and Magnetic Memory Based on Nanometer‐Thin Ferromagnetic van der Waals Fe3GeTe2 (Adv. Mater. 4/2021). Issue 4 (25th January 2021) - Zhang, Kaixuan; Han, Seungyun; Lee, Youjin; Coak, Matthew J.; Kim, Junghyun; Hwang, Inho; Son, Suhan; Shin, Jeacheol; Lim, Mijin; Jo, Daegeun; Kim, Kyoo; Kim, Dohun; et al.
Abstract : In article number 2004110, Kaixuan Zhang, Hyun‐Woo Lee, Je‐Geun Park, and co‐workers report gigantic current control of the coercive field in the van der Waals ferromagnet Fe3 GeTe2 . This results from an unusual type of gigantic spin–orbit torque (SOT) within Fe3 GeTe2 itself, which is directly related to its special symmetries, large Berry curvature, and band topology. The current‐induced SOT substantially changes the energy profile ball and suppresses the energy barrier, creating an easy path for magnetization switching and pushing the hard ferromagnet loop to a soft one. Such an effect will be extremely useful for magnetic memory and spintronics.